ISOLATION, CHARACTERIZATION AND MOLECULAR IDENTIFICATION OF MYXOBACTERIA FROM TWO OUTERMOST ISLANDS OF INDONESIA - Siti Meliah; Puspita Lisdiyanti (SEAMEO BIOTROP, 2018)
Myxobacteria are Gram negative bacteria commonly found in soil, tree bark, and decay wood. These bacteria have unique social behaviors by forming fruiting bodies, moving by gliding motility and preying on other microorganisms. The research was conducted to isolate, characterize, and identify indigenous myxobacteria from Sumba and Papua Islands of Indonesia as a preliminary step to utilize their potential in the pharmaceutical industry. Myxobacteria were isolated using filter paper and baiting with Escherichia coli to obtain cellulolytic and bacteriolytic myxobacteria, respectively. Characterization of myxobacteria was performed with Gram staining, observation on pigmentation, morphology of vegetative cells, fruiting bodies, and myxospores. Molecular identification was conducted based on 16S rRNA gene sequence analysis. A total of 10 myxobacterial strains were successfully isolated and purified. All isolates obtained were Gram negative, rod shaped with yellow or orange pigmentation. Fruiting bodies observed contained spherical myxospores. Molecular identification of these bacterial strains showed that they belong to myxobacteria from suborder Cystobacterineae, namely Myxococcus fulvus, Myxococcus stipitatus, and Melittangium lichenicola. To our knowledge, this is the first record of their occurrence in Indonesia.